EFFECTS OF NYUMBA KUMI INITIATIVE ON SECURITY MANAGEMENT IN KENYA, A CASE STUDY OF LUNGALUNGA SUB-COUNTY - Munyao, Festus M.; Ng'ang'a, Dr. Robert (Journal of Public Policy and Administration, 2017)
Purpose: The study sought to find out the effects of Nyumba kumi initiative on security management in Kenya, a case of Lungalunga in Kwale sub-County. Methodology: Descriptive research design was used where a sample of 61 respondents was selected using a simple random sampling technique. Primary data was collected using open and closed ended questionnaires from Nyumba Kumi clusters that had been established. Data collected was analyzed using a software SPSS version 20 where data was presented in frequency tables, bar graphs and pie charts. Results: The findings of this study revealed that surveillance influences security management in the various ways. Majority of respondents 45(69.2%) agreed that use of surveillance helps to detect crime beforehand thus management of security is enhanced. This study also revealed that surveillance helps in intelligence gathering as supported by over 50% of the community members in Lungalunga sub-county who subscribed to the view that surveillance helps in intelligence gathering. Similarly, the findings observed that majority (95.4%) of the respondents in Lungalunga Sub County believed and supported the fact that peace building not only helps in identifying but also in prioritizing community problems.It also agreed that policing influences security management by 93.8% while accountability influence by 66.72%. Policy recommendation: This study observed that Nyumba kumi strategy is working successfully in Lungalunga sucounty however the government should allocate financial resources to facilitate creation of awareness among the wananchi to safe on gains achieved and build more potential for future.